Rapid Preliminary Sailplane Design using Regression Method - Mohamad Yamin; Ahmad Fakhri Giyats (The Indonesian Institute of Science and Technology Research, 2022)
The article describes a new method for the preliminary design of a Sailplane based on technical data from similar Sailplanes, enabling quick design using regression methods. The authors chose FX 66-168 as the main wing airfoil for a new sailplane with a gross weight of 602 kg with a flight parameter Angle-of-Attack (AoA) 00 in minimum velocity of 49.5 m/s to cruise. As an example, we illustrate the proposed regression method. Our method allows for improving the effective preliminary design of the sailplane. The effectiveness evaluation validation of the new model is conducted with the numerical calculation using XFLR Opensource software. The research results improve design techniques and could be used as a manual for an aircraft designer.